UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN JARAK PAGAR (Jatropha curcas L) TERHADAP BAKTERI Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Dan Salmonella typhi ATCC 1408 - Maulita Cut Nuria; Arvin Faizatun; Sumantri . (Universitas Wahid Hasyim, 2009)
Jatropha curcas L is a plant species that can be used for curing, since it contains flavonoid, saponin, and tanin. Jatropha multifida L is proved to have antibacterial activities (Sisunandar, et.al., 2002). This research was intended to find out the antibacterial activities of ethanol extracts of Jatropha curcas L leaves on bacteria Staphylococus aureus, Escherichia coli, and Salmonella typhi, find out the effectiveness of those antibacterial activities and identify the compound groups contained in the ethanol extracts, the result of antibacterial activity of ethanol extracts of Jatropha curcas L was analized by statistic. Employing a maceration method, Jatropha curcas L leaves were extracted using ethanol 70% for five days. Employing an agar-diffusion method aided by disk papers and in order to find out the inhibitory area diameters of the extracts, the extracts were then tested for their antibacterial activities. Qualitative analysis on the chemical contents of the extracts were conducted employing. TLC method aided by silica-gel stationary phases for saponin and tanin and cellulose phases for flavonoid. The motion phases used ethyl acetat-acidformiat-acid acetat-water for flavonoid, chloroform-methanol for saponin and buthanol-acid acetat-water for tanin. The result of the test on antibacterial activities were analyzed statistically using Kruskall Wallis and Mann & Whitney tests. The analysis showed that ethanol extracts of the Jatropha curcas L leaves inhibited the growth of Staphylococcus aureus but not the growth of Eschericia coli and Salmonella typhi. The testing concentrations of 20%, 40%, 60%, 80%, and 100% b/v produed inhibitory area diameters averaging 8.25, 9.25, 11.00, 13.25, and 19.00 mm respectively. The positive control of Ampicillin produced an average inhibitory area diameters of 40.00 mm while the solvent control did not produce any inhibitory area diameters. Statistical test showed that there were significant differences among the different concentrations of the extracts.Thin Layer Chromatography tests produced yellow color showing the existence of flavonoid, bluish violet color showing the existence of saponin, and grayish green color showing the existence of tanin. Keyword : ethanol extracts of Jatropha curcas L leaves, inhibitory area diameters, Staphylococcus aureus, Escherichia coli, and Salmonella typhi